Analisis Perencanaan Produksi dan Perencanaan Bahan Baku untuk Meminimalkan Biaya Produksi pada UD. Tunggal - Freda Julia Najah; Sajiyo Sajiyo (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
UD. Tunggal is a small-scale cracker industry in Gresik that still applies traditional production planning and raw material procurement. This condition leads to imbalances between production and demand, as well as excess raw material inventory. This study aims to develop optimal production planning using Moving Average forecasting, Aggregate Planning (Chase Strategy), and Master Production Schedule (MPS), as well as raw material planning using Economic Order Quantity (EOQ) and Silver Meal methods. Data covers the period March 2025–February 2026. The Moving Average method yielded MAD 222, MSE 67,271.8, and MAPE 7.48%. Chase Strategy aggregate planning resulted in a total cost of IDR 498,613,684.21, lower than Level Strategy at IDR 499,016,923.70. The implementation of the Silver Meal method resulted in a total inventory cost amounting to IDR 1,063,672,375, which is 22.43% more efficient than the company's current policy. Estimated lost sales during the study period reached 672 packs with a financial loss of IDR 53,760,000.